Comparing methods to place adaptive local RTC actuators for spill volume reduction from multiple CSOs. Issue 1 (24th November 2021) - Eulogi, M.; Ostojin, S.; Skipworth, P.; Kroll, S.; Shucksmith, J. D.; Schellart, A.
Abstract: The selection of flow control device (FCD) location is an essential step for designing real-time control (RTC) systems in sewer networks. In this paper, existing storage volume-based approaches for location selection are compared with hydraulic optimisation-based methods using genetic algorithm (GA). A new site pre-screening methodology is introduced, enabling the deployment of optimisation-based techniques in large systems using standard computational resources. Methods are evaluated for combined sewer overflow (CSO) volume reduction using the CENTAUR autonomous local RTC system in a case study catchment, considering overflows under both design and selected historic rainfall events as well as a continuous 3-year rainfall time series. The performance of the RTC system was sensitive to the placement methodology, with CSO volume reductions ranging between −6 and 100% for design and lower intensity storm events, and between 15 and 36% under continuous time series. The new methodology provides considerable improvement relative to storage-based design methods, with hydraulic optimisation proving essential in relatively flat systems. In the case study, deploying additional FCDs did not change the optimum locations of earlier FCDs, suggesting that FCDs can be added in stages. Thus, this new method may be useful for the design of adaptive solutions to mitigate consequences of climate change and/or urbanisation. HIGHLIGHTS: Genetic algorithm (GA) method gives improved performance over volume approaches. A screening method is utilised to increase efficiency of the GA. The new optimisation-based methodology proved suitable for adaptive design. A local real-time control system is shown to reduce overflow spill volume.